Immunohistochemical localization of substance-P, somatostatin, enkephalin, and serotonin in the spinal-cord of the northern leopard frog, Rana-pipiens - Ho, R.H.; Cruce, W.L.R.; Adli, D.S.H.; Rosenthal, B.M.; Yuen, G.L. (1988)
Using the indirect antibody peroxidase-antiperoxidase method of Sternberger, we localized substance P (SP), somatostatin (SOM), enkephalin (ENK), and serotonin (5HT, 5-hydroxytryptamine) in the spinal cord of Rana pipiens. This is the first study to demonstrate all four substances in adjacent sections of frog spinal cord. The distribution patterns of ENK, SP, SOM, and 5HT in our study differ from that described for laminae I and II in amniotes. A high density of ENK, SP, and SOM fibers is present in a band ventral to the dorsal terminal field of cutaneous primary afferent fibers and slightly overlapping the ventral terminal field of muscle primary afferent fibers. However, a high density of 5HT fibers is present in the dorsal terminal field.